2020
DOI: 10.1101/2020.05.10.20093161
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological Distress during the COVID-19 pandemic in France: a national assessment of at-risk populations

Abstract: Background: More than 2.5 billion people in the world are currently in lockdowns to limit the spread of the novel coronavirus disease 2019 . Psychological Distress (PD) and Post-Traumatic Stress Disorder have been reported after traumatic events, but the specific effect of pandemics is not well known. Objectives:The aim of this study was to assess PD in France, a country where COVID-19 had such a dramatic impact that it required a country-wide lockdown. Methods:This study was a survey conducted in France betwe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 25 publications
3
22
1
Order By: Relevance
“…The present data are in line with data from other countries in the context of the pandemic, and provide additional evidence of the mental health burden of the COVID-19 pandemic (Chaix et al, 2020;Filgueiras and Stults-Kolehmainen, 2020;Garcia-Priego et al, 2020;Jia et al, 2020;Jung et al, 2020;Moreira et al, 2020;Newby et al, 2020;Qiu et al, 2020;Rossi et al, 2020a;Rossi et al, 2020b;Sigdel et al, 2020;Suryadevara et al, 2020;Tan et al, 2020;Ueda et al, 2020;Vahedian-Azimi et al, 2020;Wang et al, 2020a). However (and even though we did not perform a comparative study between countries), there is no evidence from the local Saudi data that the strict curfews and restrictions have led to more severe psychological distress in the KSA than in other countries.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The present data are in line with data from other countries in the context of the pandemic, and provide additional evidence of the mental health burden of the COVID-19 pandemic (Chaix et al, 2020;Filgueiras and Stults-Kolehmainen, 2020;Garcia-Priego et al, 2020;Jia et al, 2020;Jung et al, 2020;Moreira et al, 2020;Newby et al, 2020;Qiu et al, 2020;Rossi et al, 2020a;Rossi et al, 2020b;Sigdel et al, 2020;Suryadevara et al, 2020;Tan et al, 2020;Ueda et al, 2020;Vahedian-Azimi et al, 2020;Wang et al, 2020a). However (and even though we did not perform a comparative study between countries), there is no evidence from the local Saudi data that the strict curfews and restrictions have led to more severe psychological distress in the KSA than in other countries.…”
Section: Discussionsupporting
confidence: 88%
“…Chinese studies have shown that approximately 35-50% of people have experienced psychological distress owing to the COVID-19 pandemic (Qiu et al, 2020;Wang et al, 2020a). High rates of psychological distress have also been reported in Australia (Newby et al, 2020), Italy (Rossi et al, 2020a;Rossi et al, 2020b), Mexico (Garcia-Priego et al, 2020), the UK (Jia et al, 2020), Singapore (Chew et al, 2020;Tan et al, 2020), France (Chaix et al, 2020), Germany (Jung et al, 2020), Portugal (Moreira et al, 2020), Brazil (Filgueiras and Stults-Kolehmainen, 2020), Japan (Ueda et al, 2020), India (Chew et al, 2020;Suryadevara et al, 2020), Nepal (Sigdel et al, 2020) and Iran (Vahedian-Azimi et al, 2020). The mental health burden includes stress, anxiety, depression, post-traumatic stress disorder (PTSD) and insomnia.…”
Section: Introductionmentioning
confidence: 99%
“…11 Our focus on GDP reflects both the ubiquity of this measure and a lack of available, robust, economic estimates of the wider welfare impacts of lockdown. To better understand some of those wider costs, we direct the interested reader to: Branley-Bell and Talbot, 2020; Burki, 2020; Cash and Patel, 2020;Chaix et al, 2020;McLay, 2020;Pancani et al, 2020;Pinto and Jones, 2020;Sud et al, 2020;Van Lancker and Parolin, 2020. While driven out of necessity, we think that a focus solely on GDP is also justified.…”
Section: Modelling Deaths Across For Different Lockdown Datesmentioning
confidence: 99%
“…Hence the true economic costs are more diverse and quite possibly more severe than that captured by financial metrics alone. They include negative ramifications for people's mental health (Pancani et al 2020;Chaix et al 2020;Branley-Bell and Talbot 2020); increased prevalence of domestic violence (McLay 2020); and likely reduce the educational achievement of today's children (Pinto and Jones 2020;Van Lancker and Parolin 2020). As with previous financial crises (Hoynes et al 2012) and pandemics (Nikolopoulos et al 2011), the virus and the economic fall-out are disproportionately affecting people from disadvantaged groups and lower-income households.…”
Section: Introductionmentioning
confidence: 99%
“…4 Factors like lockdown, social isolation, disruptions in life routines may cause peritraumatic distress (PD). 5 It is defined as emotional and psychological distress during or immediately after any traumatic event and may develop into post-traumatic stress disorder (PTSD). 6 Study from China reveals that 35% (N=52,730) experienced PD related to COVID-19.…”
Section: Introductionmentioning
confidence: 99%